Chia seed (Salvia hispanica L.) supplementation may contribute to raising the levels of vitamin B12: An option for the vegan diet - Ahmet DEMIR, Enver; BILGIC, Yasemin (Revista de Nutrição, 2023)
Objective The chia seed, an ancient pseudocereal, is rich in omega-3 fatty acids and polyphenols, and has been suggested to possess several health benefi ts. Although it has gained popularity among nutritionists, little is known about the systemic effects of chia and their interactions. Hence, hepatorenal indicators and plasma vitamin concentrations in chia-supplemented aluminum-exposed rats were investigated. Methods Wistar albino rats were either fed on a chia-rich- or standard-diet for 21 days and exposed to aluminum. Liver function tests (Alanine Aminotransferase, Aspartate Aminotransferase, Alkaline Phosphatase, Lactate Dehydrogenase), kidney function tests (Urea Nitrogen, Creatinine), and vitamin B12 and folic acid measurements were performed by using an automated analyzer. Results Aluminum exposure had no infl uence on renal function, as did chia supplementation. However, liver function was disturbed with the exposure to Aluminum and chia was of no use against it. Surprisingly, it was found that the animals fed on a chia-rich diet isplayed higher concentrations of vitamin B12 which was not the case for folic acid. Conclusion It was deduced that a chia-rich diet has no effect on the renal function and is not able to reverse aluminum-induced hepatotoxicity; however, it may be of benefit against vitamin B12 insufficiency and thus, it may offer a novel treatment option which is particularly important in the vegan diet.